FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR TAHUN 2017 – 2019 - Cynthia, Hanna; Susanti, Merry (Jurnal Paradigma Akuntansi, 2024)
Firm value is a benchmark for investors to invest their capital in the company. This study aims to examine the effect of intellectual capital, financial perfomance, sales growth, and firm size toward firm value. Sample was selected using purposive sampling method. The total sample is 120 manufacturing companies listed on the Indonesia Stock Exchange during the period 2017 to 2019, where each period consists of 40 companies, which are processed using Eviews 12. The results of the model feasibility test indicate that this study uses a random effect model as a panel data regression model. The results of this study based on multiple linear regression analysis stated that intellectual capital and sales growth have an insignificant influence on firm value, and financial perfomance and firm size have a significant influence on firm value.